Didactic Factors of Improving the Writing Competence of Future English Language Teachers - Sotvoldievich, Toshmatov Alimardon (PT. Antis International Publisher, 2024)
This study aims to investigate the didactic factors and strategies that contribute to improving the writing competence of future English language teachers. Using a mixed-methods approach, the study surveyed and interviewed pre-service teachers and analyzed their written work. The results revealed that targeted feedback, practice-oriented instruction, collaborative learning, and self-regulated learning were significant contributors to enhancing writing competence. These findings have implications for teacher education programs and the professional development of future English language teachers.